Counter-Insurgency in Pakistan: The Role of Legitimacy. (2nd January 2017) - Lieven, Anatol
Abstract: The Pakistani security forces have won their fight against the insurgency of the Pakistani Taliban, though terrorism will remain a serious problem for the foreseeable future. Victory was won not chiefly on the basis of new tactics, but of the recovery of legitimacy for the campaign among the population and the armed forces. This occurred when the war came to be seen as one waged not in the interests of the USA, but for the defence of Pakistan. In Balochistan, the nationalist insurgency has been different from and weaker than that of the Taliban—but may prove longer lasting. Military tactics in Balochistan have closely resembled those of the British Raj, and have been based with some success on fomenting tribal divisions and co-opting tribal elites.